14x/-3 y /-3
____________
7x/-4 y-3
and the whole equation is in ( ) raised to the -2
14x/-3 y /-3
____________
7x/-4 y-3
and the whole equation is in ( ) raised to the -2
Kristine -
I'm not sure I can reproduce your equation, so I'm going to answer generally:
When you have a negative exponent, then that means you take the reciprocal of what is raised to the exponent, and the exponent becomes positive. Some examples to clarify:
x^{-2} = 1/(x^{2})
1/(x^{-2}) = x^{2}
(x^{-2})/(y^{-3}) = y^{3}/x^{2 }<=== since both x and y have negative exponents, we take the reciprocal of each.
(x-3)^{-3}(y+3)^{2} = (y+3)^{2}/(x - 3)^{3} <=== since (x-3) has a negative power and is in the numerator, it moved to the denominator
(2x/3 + 5)^{2} [1/(3x/5 - 4)^{-4} ]= (2x/3 + 5)^{2} (3x/5 - 4)^{4 }<=== (3x/5 - 4) has a negative power in the denominator, so it moves to the numerator. No changes are made to the fractions within the parentheses.
Hope that helps you get started.